Implementasi Teknik Co-op Co-op dalam Meningkatkan Ketrampilan Membaca Intensif pada Mahasiswa Semester II IKIP PGRI Madiun - Rahmasari, Brigitta Septarini; Amumpuni, Rengganis Siwi (IKIP PGRI MADIUN, 2014)
This research is aimed at (1) knowing whether or not the implementation of Co-op Co-op technique can increase the studentsâ reading ability, (2) knowing the strengths and weaknesses of the implememtation of co-op co-op to teach reading at second grade students of IKIP PGRI Madiun. The reseach method is action research. The data are collected by using observation, questionaire, and interview. Then, the data are analyzed by using CCU.Â The result of the research is the coop coop technique can increase the studentsâ reading abiliy. The strengths are it can increase studentsâ motivation, it can make students active in the class. Co-op co-op refers to a variety of teaching techniques in which students work in small groups to learn academic content. In cooperative classroom, students are expected to help each other discuss and argue.With each other, to assess each otherâs understanding and fill in each otherâs undertanding.Keywords: Co-op Co-op technique, reading ability, motivation, cooperative, active